Influence of teams games tournament learning model based on Flippity media on junior high school students interests in mathematics learning - Rizky, Sisty Annisa; Purnami, Agustina Sri; Harini, Esti (Universitas Sarjanawiyata Tamansiswa, 2024)
In the context of improving student engagement and interest in mathematics, innovative teaching methods are essential. This study aims to examine: (1) students' interest in learning mathematics using a conventional teaching model, (2) students' interest in learning mathematics using a Flippity-based Teams Games Tournament (TGT) model, and (3) the effect of the Flippity-based TGT model on students' interest in learning mathematics. The research employs an experimental design with a quasi-experimental approach using a nonequivalent control group design. The population consists of eighth-grade students at SMP Muhammadiyah 4 Yogyakarta, and cluster random sampling was used to select the sample. Data were collected through observation, questionnaires, and documentation. Data analysis was conducted using a t-test. The results indicated that students' interest in mathematics with the conventional model had an average score of 68.04, categorized as average, while the TGT-based Flippity model showed an average score of 72.72, categorized as good. The hypothesis test revealed a significant effect of the Flippity-based TGT model on students' interest in learning mathematics, with a p-value of 0.036 (p < 0.05). Based on these findings, it is recommended that mathematics teachers consider implementing the TGT model with Flippity media, as this combination positively impacts students' interest in mathematics learning.